Center of mass displacement during the badminton-specific speed test - Kersting, U. G.; Bulthuis, R.; Lysdal, F. G.; Madsen, C. M. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to identify whole-body court movement strategies of elite badminton players when carrying out a badminton specific speed test. Twenty-one (12 male and 9 female) elite badminton players participated with whole-body kinematics collected using three-dimensional motion capture. Centre of Mass (CoM) total work and mean power over the whole test, and maximum and minimum CoM height were extracted. Genders were compared by t-tests and relationships between completion time and the investigated parameters were tested using Pearson correlations. Male players showed a higher lift and drop of CoM. A significant correlation was found among the male players between power and completion time. All male players exhibited greater power during the test than female players. The results illustrate a new way to quantify mechanical factors contributing to performance in badminton.